Anemia in Pregnancy and Low Birth Weight Before and During the COVID-19 Pandemic in Kalijambe - Surya, Sang Sanggita; Jamil, Nur Aisyah; Cahyanti, Dwi; Rahma, Aulia; D. S, Amalia Adityas; Dewi, Tika Minawati (Media Kesehatan Masyarakat Indonesia, 2021)
Pregnant women and infants were a vulnerable group during the COVID-19 pandemic. This research aimed to determine anemia in pregnancy and Low Birth Weight (LBW) before and during the COVID-19 pandemic and analyze their associated factors. This was a cross-sectional study used secondary data from maternal and child health records in Kalijambe Public health center, Sragen. A total of 1169 birth records from the period of 2019-2020 were collected. The chi-square and logistic regression were used to analyze the differences and significant associated factors. The prevalence of anemia in pregnancy increased from 38.33% in 2019 to 49.21% in 2020 (p=0.013). However, the LBW proportion decreased from 7.26% in 2019 to 6.02% in 2020 (p=0.415). Mother who suffered from chronic energy deficiency marked by Mid-Upper Arm Circumference (MUAC) < 23.5 cm was higher risk of anemia (aOR 1.86;95%CI 1.13-3.08). Considering the gestational age when the hemoglobin (Hb) test, anemia was more likely to be found at the second (aOR 2.59;95%CI 1.37-4.86) and third trimester (aOR 6.97;95%CI 3.98-12.20). High-risk pregnancy had higher odds of LBW (aOR 8.57;95%CI 1.65-44.37), while anemia showed no effect on LBW (aOR 1.80;95% CI 0.34-9.45). These results were adjusted for mothers’ age, parity, abortus, infection during pregnancy, high-risk pregnancy, MUAC, preterm birth, and gestational age. COVID-19 pandemic increased the prevalence of anemia in pregnancy but had no impact on LBW. Several factors for anemia and LBW were significantly associated. This finding suggests the need for early risk detection and routine, standardized, and comprehensive antenatal care.